Physico-chemical characterization of Tamarind residues (Tamarindus indica L.): nutritional and anti-nutritional potential - Iago Garcia e Silva, Emerson; Barbosa da Silva, Joelma; Macedo Albuquerque, Janiclecia; Maria Bazílio de Omena Messias, Cristhiane (O Mundo da Saúde, 2020)
The purpose of this study was to characterize tamarind residues in terms of physico-chemical aspects, phenolic proportion, and antioxidant activity, exploring its nutritional and anti-nutritional potential for human consumption. The selected fruits were weighed, and the pods were manually broken, separated from the pulps, seeds, and husks. The products were dried in an oven with air circulation (6h). The husks were crushed and submitted to granulometric sieving (250 μm) to form tamarind husk powder (THP). Regarding the seeds, a fraction was submitted to roasting (115ºC for 15 min) and another one kept in natura. Subsequently, they were crushed and subjected to granulometric sieving (250 μm) to form fresh seed powder (FSP) without roasting, and toasted seed powder (RSP). The analytical measurements were taken for the attributes: pH, titratable acidity, water activity, humidity, ash, proteins, lipids, total fiber. The antioxidant potential was determined using the free radical 2,2-diphenyl-1-picrilhidrazil, in addition to the total phenolic composition and tannins. All powders had low moisture values. THP (24.6g/100g) and RSP (15.31g/100g) showed high fiber content. In terms of protein, the RSP had a higher content (14.56g/100g). As for the phenolic compounds, these were higher in the seed powder. The tannin content was similar between powders. Powders showed high antioxidative capacity. Tamarind residues are promising, in terms of added nutritional value, and are able to supplement human diets, especially in relation to fiber, protein, energy, and antioxidant content.